Burkholderia cepacia ST 767 causing a three-year nosocomial outbreak in a hemodialysis unit - Stéfani T.A. Dantas; Gousilin R. Silva; Iranildo A. Fernandes; Ary Fernandes Júnior; José C.F. Pantoja; Carlos H. Camargo; Juliano L. Gonçalves; Ivana G. Castilho; Nathália C.C. Silva; Vera L.M. Rall (Journal of Infection and Public Health)
Background: The risk of bloodstream infections increases in patients undergoing chronic hemodialysis, primarily due to water contamination or improper handling during dialyzer reprocessing. This study aimed to identify virulence factors and gather epidemiological data on the Burkholderia cepacia complex (Bcc), isolated from water and blood cultures during an outbreak in a hemodialysis unit. Methods: We analyzed 33 Bcc isolates from blood cultures of patients with bacteremia undergoing hemodialysis and 24 isolates from water samples collected between 2019 and 2022. All isolates were tested for virulence factor-encoding genes, including cblA, esmR, zmpA, and zmpB, using polymerase chain reaction (PCR) assays. The isolates were further characterized using Multi-Locus Sequence Typing (MLST) and Pulsed-Field Gel Electrophoresis (PFGE). Biofilm production was assessed on polystyrene microplates at 20°C and 35°C. Results: The genes zmpB and zmpA were present in 100 % and 96.5 % of the isolates, respectively. However, none of the isolates carried the cblA or esmR genes. Within the Bcc, the species B. cepacia (genomovar I) was identified through recA gene sequencing. PFGE analysis revealed that all human- and water-derived isolates shared the same pulsotype, classified as ST-767. Conclusions: Despite routine water disinfection with peracetic acid, the detection of a single pulsotype of this species over three years indicates the persistent of Burkholderia cepacia ST 767 in the plumbing system, leading to the contamination of patients undergoing hemodialysis. This persistence is likely facilitated by biofilm formation, as all water-derived isolates demonstrated biofilm production at 20°C. To exacerbate the situation, all isolates exhibited multidrug resistance, further complicating patient treatment and management.